Fleet operation at ICD in relation to Kontena Nasional Sdn. Berhad / Wan Faizal Sazali Wan Mohd. Isa - Wan Mohd. Isa, Wan Faizal Sazali (1994)
The purpose of the research is to determine whether the present movement of container delivery is beneficial operationally. Comparison is made between the present movement of container delivery that is, from ICD to shipper and then back to ICD with the alternative movement, that is from ICD to shippers and then direct to Container Yard, Port Klang. At the moment, all the containers are stored at ICD, Seri Setia and consequent delivery to Port Klang. For the alternative movement, the boxes will be directly transported to Container Yard, Port Klang from the shipper's premises. The method that are used in collecting in format ion and data are observations and interviews. This study will give some guidelines in identifying which movement will contribute less problems to the Company. The findings in this research is in line with the hypothesis, that is, the Haulage Department is operating at the efficient level with the present system of modus operandi due to the faster turnaround time and higher rate of utilisation of its fleet movement.